Climate-smart agriculture for smallholder farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Climate-smart agriculture is improving the lives of millions. Find out how in our new book: Climate Smart Agriculture Success Stories: https://ccafs.cgiar.org/research-highlight/climate-smart-agriculture-improving-lives-millions-heres-how This video was produced for the Global Landscapes Forum, 16-17 November 2013. Learn more at http://www.landscapes.org.